Clinical update on risks and efficacy of anti-SARS-CoV-2 vaccines in patients with autoimmune hepatitis and summary of reports on post-vaccination liver injury. Issue 6 (June 2022) - Lleo, Ana; Cazzagon, Nora; Rigamonti, Cristina; Cabibbo, Giuseppe; Lai, Quirino; Muratori, Luigi; Carbone, Marco; ,
Abstract: Patients with liver diseases, especially those with cirrhosis, have an increased mortality risk when infected by SARS-CoV-2 and therefore anti-SARS-CoV-2 vaccine has been recommended by leading Scientific Associations for all patients with chronic liver diseases. However, previous reports have shown a reduced antibody response following the full course of vaccination in immunosuppressed patients, including liver transplant recipients and several rheumatic diseases. This document, drafted by an expert panel of hepatologists appointed by the Italian Association for the Study of the Liver (AISF), aims to present the updated scientific data on the safety and efficacy of anti-SARS-CoV-2 mRNA vaccines in patients with autoimmune hepatitis (AIH). Furthermore, given the recent reports of sporadic cases of AIH-like cases following anti-SARS-CoV-2 mRNA vaccines, we summarize available data. Finally, we provide experts recommendations based on the limited data available.